"The Meaning of Romance": Popular Song and Historical Narrative from Arthurian Literature to American Graffiti. (29th September 2016) - Valdés-Miyares, J. Rubén
Abstract : This article argues that a fundamental connection between music and narrative has existed since the age of medieval romance, and is still noticeable in the uses of popular song in modern cinema. The allusions to a code ultimately originating in medieval romance in George Lucas's American Graffiti are a key clue to unraveling a complex history going back to the longing for a lost age in Arthurian romance, through the use of song in medieval drama, nineteenth-century melodrama, and historical romance, the integration of theme songs and compilation scores in film narrative, and the nostalgia for the age of rock 'n' roll in early-1970s America. The analysis of such connections points to the perennial function of old songs, by means of their familiar tunes and their allusive words, and occasionally their links with dances, in the affective, yet also ironic, recreation of a harmonious dreamed-up past in film.